Advances in group processes - Thye, Shane R.; Kalkhoff, Will; Lawler, Edward J. (Emerald Publishing Limited, 2024)
Volume 41 of Advances in Group Processes assembles papers related to a variety of topics in small groups and organizational research. Featuring leading scholars who work in the general area of group processes, the volume includes papers that reflect a wide range of theoretical approaches and addresses issues related to how: social identity theory can be used to understand romantic "hook-up" culture and also the gendered meanings of occupations social exchange networks and the distribution of identities within impact trust among strangers the propensity to refuse or accept offers impacts the flow of benefits in reciprocal exchange fundamental status processes alter vocal accommodation, the effectiveness of female leadership, responses to discrimination, and the importance of work efficiency and physical attractiveness for women seeking status Advances in Group Processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of 'group processes.' This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, trust, justice, social influence, identity, decision-making, intergroup relations, and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, economics, business, philosophy, computer science, mathematics, and organizational behavior.
Includes index.
Keywords: Corporate culture.; Business & Economics -- Human Resources & Personnel Management.; Business strategy.; Personnel and human resources management.; elektronické knihy; electronic books